V-OG05 Robotic Hellers Myotomy. (16th December 2021) - Knight, Ben
Abstract: Background: Achalasia is a rare condition affecting less than 1:100, 000 patients. Treatment for this rare condition include balloon dilation, botox injection, endoscopic myotomy (POEMS) or surgical myotomy. Laparoscopic surgical myotomy is the "go to" approach for most surgeons; it is tried and tested, can be performed safely and quickly with a low complication rate, minimal pain and a short length of stay. Methods: This video presents the technique adopted for robotic oesophageal myotomy in a patient with type II achalasia. A 4 arm technique was adopted with arm 4 on the patients left. The Davinci X system was used in this case. A Nathensen liver retractor was used to retract the liver; robotic instruments included the hook and cadiere forceps x2. Results: The procedure was successfully performed; the operative time was 53 minutes, LOS was <24 hours. Check endoscopy revealed a wide open gastro-oesophageal junction and a long myotomy. The patient noted an improvement in symptoms with 24 hours and has had no significant reflux. Conclusion: The enhanced magnified 3D view on the robotic platform allows better visualisation of the hiatal structures, vagal nerves and muscle fibres when performing the myotomy. Using the 4 th arm to retract the lateral edge of the oesophageal muscle provides a very safe and stable platform to perform a long myotomy. I think the robotic system should be adopted as the standard approach for a hellers myotomy.